Biến đổi cấu trúc và tính chất của vật liệu compozit polyetylen tỷ trọng cao/bột gỗ gia cường bởi hạt nano TiO2 sau thử nghiệm gia tốc thời tiết - Giang, Nguyễn Vũ; Hoàng, Thái; Huynh, Mai Đức; Trung, Trần Hữu (Vietnam Journal of Chemistry, 2015)
In this study, the composites based on high density polyethylene (HDPE) and wood flour (WF) in the presence of PEgMA compatibilizer and TiO2 nanoparticles (in rutile crystal form) were investigated the accelerated weathering test. After 1.900 hours testing, tensile strength of HDPE/WF composite using PEgMA reduced siginificantly (remaining value of 55.98 %). Whereas, the mechanical properties of the HDPE/PEgMA/WF composites slightly decreased thanks to the presence of TiO2 nanoparticles, the retention of tensile strength of composite using TiO2 of 3 wt.% is 81.89 %. Calculating from Fourier transform infrared (FT-IR) spectra showed that the carbonyl index (CI) and wood index (WI) of composites without TiO2 were higher than that of composites containing TiO2. Besides, the discoloration of HDPE/PEgMA/WF composite could lead to lightening on the surface, in fact, this occurs clearly in the case of composites containg TiO2 in comparison with the sample without it. It may imply that TiO2 nanoparticles played a role as the degrading inhibitors of composites under UV irradiation. In addition, observation from the SEM images, the surface of HDPE/PegMA/WF/TiO2 composites was detroyed less than that of composites without TiO2.